Ocular complications of acoustic neuroma surgery. Issue 12 (1st December 1999) - Mulhern, M G; Aduriz-Lorenzo, P M; Rawluk, D; Viani, L; Eustace, P; Logan, P
Abstract : AIM: To analyse the risk factors involved in the development of ocular complications after acoustic neuroma resection, in particular corneal complications and visual loss, and to identify measures that may reduce these. METHODS: 62 patients who underwent surgery for acoustic neuroma had a standardised ophthalmic examination and retrospective case note review. RESULTS: At final review (mean 37.6 months), although 38 patients reported ocular symptoms, only 22% saw 6/12 or worse. Patients with hypoaesthetic corneas had a higher incidence of corneal pathology (79%) than those with normal sensation (39%). Lagophthalmos increased the incidence of corneal pathology (to 80%); in those with normal closure, the incidence was only 46%. 20 patients required at least one ophthalmic surgical procedure. CONCLUSIONS: After acoustic neuroma resection patients place a considerable burden on the ophthalmologist. Immediate referral postoperatively, and frequent review of those with abnormal sensation may reduce the severity of long term ocular complications.